Molecular cloning of WIF1 and HMGA2 reveals ear‐preferential expression while uncovering a missense mutation associated with porcine ear size in WIF1. (28th February 2019) - Liang, J.; Zhang, Y.; Wang, L.; Liu, X.; Yan, H.; Wang, L.; Zhang, L.
Summary: Considerable diversity exists in porcine ear size, which is an important morphological feature of pig breeds. Previously, we localized four crucial candidate genes— high mobility group AT‐hook 2 ( HMGA2 ), LEM domain‐containing 3 ( LEMD3 ), methionine sulfoxide reductase B3 ( MSRB3 ) and Wnt inhibitory factor 1 ( WIF1 )—on Sus Scrofa chromosome 5 affecting porcine ear size, then cloned LEMD3 and MSBR3 . In this study, we performed rapid amplification of cDNA ends to obtain full‐length cDNA sequences of 2338‐bp WIF1 and 2998‐bp HMGA2 . Using quantitative real‐time PCR, we revealed that WIF1 expression was highest in ear cartilage of 60‐day‐old pigs and that this is therefore a better candidate gene for ear size than HMGA2 . We further screened coding sequence variants in both genes and identified only one missense mutation ( WIF1: c.1167C>G) in a conserved epidermal growth factor‐like domain from the mammalian WIF1 protein. The protein‐altering mutation was significantly associated with ear size across the Large White × Minzhu hybrid and Beijing Black pig populations. When WIF1: c.1167C>G was included as fixed effect in the model to re‐run a genome‐wide association study in the Large White × Minzhu intercross population the P ‐value of the peak SNP on SSC5 from re‐running the genome‐wide association study dropped from 2.45E‐12 to 7.33E‐05. Taken together, the WIF1: c.1167C>G could be an important mutation associated with ear size. Our findings provide helpful information for further studies of the molecular mechanisms controlling porcine ear size.